2010
DOI: 10.1111/j.1365-2125.2009.03567.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential genetic risk factors in angiotensin‐converting enzyme‐inhibitor‐induced angio‐oedema

Abstract: KeywordsACE I/D polymorphism, angio-oedema, bradykinin, bradykinin B2 receptor polymorphism, serum ACE activity ---------------------------------------------------------------------- WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT• Angiotensin-converting enzyme inhibitor (ACEi)-induced angio-oedema is an underestimated clinical life-threatening problem.• The incidence of this non-allergic, bradykinin-induced drug side-effect is 1 : 4000.• Although most ACEi-treated patients probably have an increased bradykinin plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
1
22
0
1
Order By: Relevance
“…Intradermal injection of substance P induces wheal and flare reactions in normal human skin 90, 91. Genetic variation in the ACE gene has been studied in patients with angioedema and CU patients with angioedema 92-94. Insertion/deletion polymorphisms of the ACE gene showed statistically significant associations with angioedema in CU in a Turkish cohort 94.…”
Section: The Candidate Gene Approach In Cumentioning
confidence: 99%
“…Intradermal injection of substance P induces wheal and flare reactions in normal human skin 90, 91. Genetic variation in the ACE gene has been studied in patients with angioedema and CU patients with angioedema 92-94. Insertion/deletion polymorphisms of the ACE gene showed statistically significant associations with angioedema in CU in a Turkish cohort 94.…”
Section: The Candidate Gene Approach In Cumentioning
confidence: 99%
“…This association has been replicated in a larger cohort ( n = 169), and the C-2399A genotype was associated with an increased risk of angioedema in men only (OR 2.17 1.09-4.32, p = 0.03) [ 163 ] . Studies that have investigated whether ACE or bradykinin B 2 gene polymorphisms are associated with development of angioedema have, to date, found no causal association [ 164,165 ] . Due to the rarity of this condition, the sample sizes were small (maximum 65), and hence, a larger population would be required to de fi nitively exclude this association and identify new associations.…”
Section: Ace Inhibitor-induced Angioedemamentioning
confidence: 98%
“…106 The risk associated with the haplotype is higher compared to the rs3788853 alone (4.9-fold vs 3.0-fold) 95 Moholisa (2013) genotype, in which both copies of the ACE gene lack the 287 base-pair indel region, is associated with higher ACE activity, but not with higher risk of ACEi-A. [96][97][98] One of these studies reported a 50% lower ACE activity in ACEi-A cases compared to controls taking the same drug, and independent of the presence of the insertion/deletion variation 98 and, the two other studies failed to replicate this finding. 109 However, three further case-control studies did not support these initial findings.…”
Section: Ace Genementioning
confidence: 99%